INSURERS AS FINANCIAL INTERMEDIARIES: STRUCTURES, CONDUCT, AND ECONOMIC PERFORMANCE - Harchaoui, Tarek M. (Assurances)

(untitled) (HEC Montréal, 1997)
Insurance companies are engaged in a joint activity. They provide financial protection to economic agents and perform a financial intermediation activity. Much like banks, insurance companies transform liabilities (reserves) into earning assets; they acquire funds at periodic intervals on a contractual basis and invest in portfolios of financial assets. Despite its importance, the financial intermediation activity of insurance companies has rarely been examined for its own right. Most of the studies currently available on insurance companies typically restrict their focus to only the financial protection activity. The contribution of the financial intermediation activity to the economic performance of the insurance companies as a whole is usually taken as given. The purpose of this paper is to examine the structures of the Canadian financial intermediation industry and the economic performance of insurance companies' financial intermediation activity. Despite the dramatic loss of ground of life insurance within the market of contractual savings as a result of the various tax policies that have been implemented during the eighties, and despite strong competition from mutual funds and trusteed pension funds, insurance companies' financial intermediation activity experienced a remarkable growth and their market share remained steady. This perfomance can be attributed to the combination of a comparative advantage in the market of RRSPs and an enviable 1.17 average annual growth of multifactor productivity during the period 1985-1994.